Association of N, N-diethyl-m-toluamide (DEET) with obesity among adult participants: Results from NHANES 2007–2016. (November 2022) - Cui, Qianwei; Zhu, Xu; Guan, Gongchang; Hui, Rutai; Zhu, Ling; Wang, Junkui
Abstract: Background: The purpose of this study was to examine the relationship between N, N-diethyl-m-toluamide (DEET) exposure and obesity-related outcomes in the general adult population using the data from the National Health and Nutrition Examination Survey (NHANES). Methods: This cross-sectional study examined the data from the NHANES from 2007 to 2016 and totally evaluated 8, 770 individuals. DEET's primary oxidative metabolite, 3-(diethylcarbamoyl) benzoic acid (DCBA), is a sensitive and specific indicator of DEET exposure. DCBA was divided into three groups based on the interquartile range. Body mass index (BMI) and waist circumference (WC) were used to define obesity and abdominal obesity, respectively. The association among DCBA and obesity-related outcomes was evaluated using a multivariable linear and logistic regression model. Results: Overall, median age of participants was 46.0 (IQR 31.0, 59.0) years, with 4295 (49.2%) men, while median BMI and WC were 27.8 (24.0, 32.0) and 29.6 (86.6, 108.1) kg/m 2, respectively. Approximately 3, 251 (35.9%) cases of obesity and 4, 778 cases (54.4%) of abdominal obesity were observed. In multivariable-adjusted linear regression models, as the tertiles of DCBA increased, BMI and WC monotonically increased regardless of the adjustments (all p for trend <0.01). By referring the lowest tertile of DCBA, the highest tertile was associated with a higher BMI (β = 0.83, 95% confidence intervals [CI] [0.45, 1.21]; p < 0.001) and WC (β = 1.59, 95% CI [0.59, 2.60]; p = 0.002). The multivariate odds ratios (95% CI) for obesity increased monotonically as 1.18 (0.97–1.44) and 1.36 (1.15–1.61) ( p for trend 0.001). Similar associations between DCBA and the prevalence of abdominal obesity were observed across increasing DCBA tertiles compared with the reference tertile (OR = 1.22, 95% CI [1.02, 1.44]; OR = 1.28, 95% CI [1.08–1.54]; p for trend = 0.002). Conclusions: These findings suggested that higher DCBA concentrations are positively associated with the prevalence of obesity and abdominal obesity in the general adult population. Graphical abstract: Image 1 Highlights: DEET exposure was associated with obesity-related outcomes. Higher DCBA levels were positively associated with the prevalence of obesity and abdominal obesity. Additional research is required to confirm these findings and to elucidate the underlying mechanism.